Ca(2+)- and GTP-dependent exocytosis in mouse pancreatic beta-cells involves both common and distinct steps. - Proks, P; Eliasson, L; Ammälä, C; Rorsman, P; Ashcroft, F (1996)
1. The effects of GTP and Ca2+ on secretion from single pancreatic beta-cells were studied using capacitance measurements as an indicator of exocytosis. 2. GTP or GTP gamma S produced a concentration-dependent increase in cell capacitance in the absence of intracellular calcium. There was no effect of cyclic AMP or BAPTA an GTP-induced secretion. 3. In the absence of GTP, the relationship between intracellular calcium concentration and the maximum rate of secretion was fitted by the Hill equation with a slope factor of 2.5 and half-maximal activation at 1.6 microM intracellular Ca2+. Similar values were obtained in the presence of GTP gamma S, suggesting GTP does not alter the sensitivity of the secretory machinery to Ca2+. 4. GDP beta S alone had no effect on cell capacitance but caused a dose-dependent inhibition of exocytosis induced by infusion of either GTP gamma S or Ca2+, suggesting both stimuli involve G-protein activation. GDP beta S was without effect on exocytosis evoked by depolarization-mediated Ca2+ entry. 5. The time course of exocytosis following rapid elevation of GTP gamma S by photolysis of a caged precursor was dependent on the intracellular Ca2+ and cyclic AMP concentrations. 6. Our results are interpreted in terms of a model in which the secretory pathways stimulated by Ca2+ and GTP contain both common and separate parts.